Progress in Green Economics - George, Babu (Bentham Science Publishers, 2022)
Green economics refers to the discipline in which economists and businesses pursue policies that are conducive to minimizing environmental and ecological damage and therefore sustainable development. Progress in Green Economics primarily focuses on developments in the transition of different industries and sectors to a sustainable, environment-friendly economic model. The book presents 7 chapters that cover different topics that reflect these developments in the field from a number of academic and practical angles. The topics covered in the book include a review of the Food Energy Water Waste (FEWW) paradigm in Asian countries, an analysis of green economic forces in the Arctic region, green economics for protected area tourism, a conceptual analysis of green economics strategy, sustainable development and green banking in South Africa, and six sigma methodology for implementing green economic policies in different industries. Each chapter is organized into reader-friendly sections and is supplemented with references for the benefit of more involved scholars. The multi-regional perspectives, along with the theoretical and practical information on the topic make this reference a timely and handy resource on green economics and sustainable development for academics, scholars, industrialists, policymakers and economics enthusiasts alike.